MINERALOGICAL PROPERTIES OF OAK FOREST SOILS IN IRAQI KURDISTAN REGION - & et al., Abdullah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was conducted from 1/7/2016 to 20/12/2018 to study the mineralogical properties of oak forest at 12 locations (Gara, Matin and Brifca) from Dohuk governorate, (Bilah, Malakan and Awagrd) from Hawler Governorate, (Bardanga, Badawan and Chwarta) from Sulaimani Governorate, and (Bakhakon, Hawar and Sartak) from Halabja governorate in Iraqi Kurdistan region. The samples collected from a depth of (0 – 60) cm for laboratory analysis. The study includes qualitative identification of clay minerals by X- ray diffraction data. Peak height was used as a rough indicator of relative abundance of minerals. In general, the expansion of 14°A to ≈ 17°A in ethylene glycol treatment was not detected because the measuring was started from 5θ (degree 5 theta) so the differentiation between Chlorite and Semectite was not done in this treatment. The main results indicated that the swelling chlorite being the dominant mineral in these soils. While the miner clay mineral in that locations were Kaolinite. Mica was identified in all location except of Bilah site, the dominant type of Mica was Muscovite which was obtained from 6 Locations, while Biotite obtained from 5 sites. It appears that Muscovite was recorded from 50% of Forest sites while Biotite recorded at 41.7% of Forest sites and Both Mica mineral type was not recorded from 8.3% of studied Forest soils.